Culturally Relevant Pedagogy: A Model To Guide Cultural Transformation in STEM Departments - Angela Johnson (American Society for Microbiology, 2020)
Despite recent interest and pressing need, we lack a clear model of culturally relevant, responsive, sensitive teaching in university STEM departments. Most culturally relevant efforts within STEM education address actions individual professors can take within their own classrooms and mentoring, rather than describing how to go about enacting cultural transformation at the departmental level. In this article, we propose the application of the Ladson-Billings model of culturally relevant pedagogy to promote an inclusive culture within undergraduate STEM departments. The model consists of three components: academic success, cultural competence and integrity, and critical consciousness. We define each component and describe what it looks like and how it can be used to guide departmental transformation, including examples in biology, physics, mathematics, and computer science departments at our own institution. This model can help guide faculty committed to creating departments where all kinds of STEM students can thrive, provided they are willing to work hard.